What the fishing boats have in common: a classroom experiment. (2018) - Lewis, Caleb
Pluralism in the economics classroom should be effectively supported by active learning exercises. This paper describes a classroom experiment that involves students in an incentivised common goods environment in a context familiar to students from diverse backgrounds: overfishing. This exercise can provide a learning moment that draws from the varied experiences and world-views of the participants and varied theoretical approaches including those outside mainstream economics. In each round of the game, students individually choose between fishing aggressively and conservatively. Fishing aggressively depletes a school of fish to such an extent that it will not replenish. Students are rewarded with points in proportion to their catch to simulate the returns to private fishing boats. The result is an effective and engaging learning opportunity particularly suitable to undergraduate economics courses. This exercise is an example of how pluralism can be incorporated in pedagogy.